DOES CORPORATE GOVERNANCE AFFECT CORPORATE FINANCIAL PERFORMANCE? THE MODERATING ROLE OF BOARD CONNECTION POLITIC - Olga Yolenta (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
This study aims to determine the effect of corporate governance on company performance with political connections as moderation. Corporate governance assessment variables include the women's board and board size. The company's performance variable is measured by Return on Assets (ROA). The population of this study are companies listed on the Indonesia Stock Exchange for the 2017-2021 period with a total sample of 395 data. Research data were obtained from financial and annual reports published on the official website of each company. Panel regression is used as a data analysis method in this study. The results of the study show that there is a significant positive effect on the board size variable on company performance. In contrast to the female board variable which has no significant effect on company performance.